(untitled) (Journal of The Colloquium for Information Systems Security Education, 2018)
In the modern world of exponentially increasing threats from advanced technologies, many institutions recognise the need for establishing cyber security programs to meet the growing demand for cyber security professionals in industry, government and defence organisations. However, cyber security, cyber defence and cyber war education is still ill represented in Australia. Some directions to overcome the problem is given by the Australian Government (Australia’s Cyber Security Strategy)[1] but not yet fully developed. To address this issue, the Australian Centre for Cyber Security (ACCS) at the University of New South Wales (UNSW) Canberra at ADFA has been developing a suite of three postgraduate cyber security programs for the steadily increasing numbers of students from diverse backgrounds interested in studying cyber security and acquiring cyber warfare skills. The Centre is the only one in the world that offers a university degree specialising in cyber war and peace. This paper will describe the structured approach of developing the programs, highlight challenges by providing observations and lessons learned over the past two years, and propose some future directions on how to overcome these challenges.